Processing Training Zero Waste Becoming a Craft Product of Economic Value for Coastal Women in Lalowaru Village - Asriyana, Asriyana; Haya, La Ode Muhammad Yasir; Oetama, Dedy; Arsal, La Ode Muhammad (Abdi Masyarakat, 2023)
Liquid and solid waste is still a problem today. The existence of waste pollution can damage the environment, bring natural disasters, disrupt public health and other living things. An example of solid waste is garbage that is often found both in the yard of the house and around the coast. Inorganic waste has a decomposition time of 1 years to more than 1,000 years because it is made of chemicals so that bacteria are unable to decompose it. If inorganic waste is burned, air pollution will occur because the smoke produced can interfere with public health. The purpose of this service is to introduce the application of zero waste which can be a product that can improve the household economy of the Lalowaru Sub-District. This activity was carried out by conducting a demonstration of making handicrafts. The results of the service show that with this training, service participants get an educational understanding of waste that can be processed into handicraft products that have added value.